Pengaruh Program Aktivitas Fisik dengan Pendekatan Pola Bermain terhadap Kebugaran Jasmani Siswa Sekolah Dasar - Ma’arif, Ilmul; Setyawan, Risfandi (MAN Insan Cendekia Jambi, 2025)
The purpose of this study was to see the results of a physical activity programme with a pattern approach to physical fitness, the method of experimental research type with a quantitative approach and research design One Group Pretest-Posttest Design. Samples of upper grades with ages 10-12 years of ardirejo public elementary school students with a total of 81 students, data collection with TKJI ages 10-12 years, data analysis with descriptive statistics, test scores and test norms (TKJI) and hypothesis testing with paired t-test. The results for the pre test results were obtained in the less category with 32 students (39.51%) and for the post test (moderate category 42 students (51.85) while for hypothesis testing the results obtained a sig value of 0.00 <0.05, so it can be concluded that there is an effect of physical activity programmes on students' physical fitness.